2010
DOI: 10.1667/rr2006.1
|View full text |Cite
|
Sign up to set email alerts
|

DNA Copy Number Aberrations and Disruption of the p16Ink4a/Rb Pathway in Radiation-Induced and Spontaneous Rat Mammary Carcinomas

Abstract: Chromosomal amplifications and deletions are thought to be important events in spontaneous and radiation-induced carcinogenesis. To clarify how ionizing radiation induces mammary carcinogenesis, we characterized genomic copy number aberrations for gamma-ray-induced rat mammary carcinomas using microarray-based comparative genomic hybridization. We examined 14 carcinomas induced by gamma radiation (2 Gy) and found 26 aberrations, including trisomies of chromosomes 4 and 10 for three and one carcinomas, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
2
10
2
Order By: Relevance
“…Our aCGH analysis revealed copy number aberrations in mammary carcinomas of rats. The number of aberrations we detected here is greater than what we reported previously (24) possibly due to the increased number of cancer cells we isolated using laser microdissection. We found that these aberrations were present in a variety of genes that are frequently affected in human breast cancer (22), thus supporting the idea that these aberrations play important functional roles in the development of carcinomas in rats.…”
Section: Discussioncontrasting
confidence: 83%
“…Our aCGH analysis revealed copy number aberrations in mammary carcinomas of rats. The number of aberrations we detected here is greater than what we reported previously (24) possibly due to the increased number of cancer cells we isolated using laser microdissection. We found that these aberrations were present in a variety of genes that are frequently affected in human breast cancer (22), thus supporting the idea that these aberrations play important functional roles in the development of carcinomas in rats.…”
Section: Discussioncontrasting
confidence: 83%
“…However, direct comparisons of the current results with published results in aCGH are practically difficult because the results of aCGH analyses are greatly influenced by the array design and type of samples (e.g., fresh frozen or FFPE). A previous study of an aCGH analysis of radiation-induced and spontaneous rat mammary carcinoma indicated that the frequency of carcinoma having any CNA and the number of CNA in radiation-induced carcinoma were significantly greater than that observed in the spontaneous carcinoma [34]. Another study of an aCGH analysis of premenopausal breast cancers in the residents from a nuclear fallout-contaminated area in Belarus did not show any significant differences or tendencies in the average number of total DNA CNA compared with matched control cases from Western New York, even though breast cancer from Belarus had significantly more average number of gains [35].…”
Section: Discussionmentioning
confidence: 99%
“…Images were Western blotting. Western blotting was performed as previously described (17). Cells were lysed using Complete Lysis-M, EDTA-free (Roche diagnostics, Mannheim, Germany) according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%